Pengaruh Model Problem Based Learning Terhadap Hasil Pembelajaran Menulis Teks Eksposisi SMA Negeri 8 Makassar - Ikha Indawati; Hajrah; Evi Susianti (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
The Influence of Problem Based Learning Model on Writing Skills of Exposition Texts of Class XII SMA Negeri 8 Makassar aims to: (1) describe the writing skills of exposition texts of Class XII students of SMA Negeri 8 Makassar before using the problem based learning model; (2) describe the writing skills of exposition texts of Class XII students of SMA Negeri 8 Makassar after using the problem based learning model; and (3) test the influence of using the problem based learning model on the learning outcomes of writing exposition texts of Class XII students of SMA Negeri 8 Makassar. This research is a type of quantitative research. The research design used is the One Group Pretest-Posttest Design. The results of data analysis show that: (1) the learning outcomes of learning to write exposition texts of Class XII students of SMA Negeri 8 Makassar before using the problem based learning model are categorized as less skilled with an average value of 63.75; (2) the learning outcomes of learning to write exposition texts of Class XII students of SMA Negeri 8 Makassar after using the problem based learning model are categorized as quite skilled with an average value of 84.35; (3) the results of the hypothesis test show that the sig. (2-tailed) value is 0.000 < 0.05, so the alternative hypothesis (Ha) is accepted, namely that there is an influence of the use of problem-based learning on the learning outcomes of writing expository texts for Class XII students of SMA Negeri 8 Makassar. problem-based learning model, writing skills, expository text